ANALISIS TANTANGAN GURU IPA SMP DI INDONESIA DALAM MENERAPKAN PEMBELAJARAN IPA TERINTEGRASI STEM - Niken Kartika Candra; Clarissa Jeanny; Mochamad Setiawan; Nur Ahmad (FKIP e-PROCEEDING, 2022)
The implementation of STEM in Indonesia is still recently implemented before it was only a discussion of articles because there were challenges for teachers in its application. Therefore, this research was conducted to map all articles published online with the theme of implementing STEM education in Indonesia. This research method is carried out by summarizing articles from various reputable scientific journals. The next step in processing the reference sources obtained, namely the stage of collecting data, analyzing data, inferring the content of the data, and responding to the data scientifically. Five articles discussing STEM Implementation in Indonesia were selected using journal data from the keywords "implementation" + "Stem Education" + "Indonesia" were selected to capture and reach as many relevant studies as possible regarding the implementation of Stem Education in Indonesia. After the collection of article data, the findings of the study are summarized, identified, and then presented quantitatively as well as descriptively. The results showed that teachers' skills and knowledge are still relatively low in applying STEM-integrated science learning. In addition, teachers lack knowledge of the digital resources that can be used to implement STEM-based science learning, teachers do not have the skills to create STEM-based learning tools, teachers do not have adequate insight into STEM-based learning, and lack of support for means/media/props to support STEM implementation. Therefore, stimulation and mentoring to students and teachers is needed so that STEM education can touch all fronts.